Pineal Parenchymal Tumor with Intermediate Differentiation—A Case Report and Review of Literature from Rural India - Kumar, Raj; Dayal, Seema; Krishna, Mani (Indian Journal of Neurosurgery, 2019)
Pineal gland tumors are rare tumors. According to World Health Organization (WHO) classification (2016) of the central nervous system, pineal parenchymal tumors of intermediate differentiation (PPTID) occupied their position between pineocytoma and pineoblastoma. It is either grade II or III. There are small numbers of reported cases, so its classification is still a matter of controversy. Here, we report a case of a 35-year-old man who presented with complaints of headache, nausea, vomiting, and focal weakness for 1 year. Computed tomography revealed an enhancing mass lesion in the region of pineal gland along with hydrocephalus. Following operation, histopathology of excised specimen was done, and it showed cellular tumor. Cells were having larger nuclei, vesicular chromatin pattern, ample cytoplasm, focal neuropil-like stroma along with moderate atypia, 3 to 5 mitotic figures per 10 hpf (high-power field), marked vascular proliferation, and pseudo rosette. Immunohistochemistry was found strongly positive for glial fibrillary acidic protein (GFAP) and neuron-specific enolase (NSE), variable for synaptophysin, and negative for neurofilament and epithelial membrane antigen (EMA). These findings confirmed the diagnosis. As this tumor is rare with uncertain behavior following available treatment, the case report of PPTID grade III large cell type may enrich the existing data and is being presented because of its rarity.
Keywords: pineal parenchymal tumors; pineal parenchymal tumor of intermediate differentiation; tumor grade III